2022
DOI: 10.1063/5.0087571
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of β-Ga2O3 by hot-wall MOCVD

Abstract: The hot-wall metalorganic chemical vapor deposition (MOCVD) concept, previously shown to enable superior material quality and high performance devices based on wide bandgap semiconductors, such as Ga(Al)N and SiC, has been applied to the epitaxial growth of β-Ga2O3. Epitaxial β-Ga2O3 layers at high growth rates (above 1 μm/h), at low reagent flows, and at reduced growth temperatures (740 °C) are demonstrated. A high crystalline quality epitaxial material on a c-plane sapphire substrate is attained as corrobora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…The results indicated that the slightly distorted unit cell of β-Ga 2 O 3 could be epitaxially grown on the GaN/A 2 O 3 substrate, which might require a relaxation technology of the β-Ga 2 O 3 unit cell to improve device performance. To alleviate the shape-related issues of the β-Ga 2 O 3 growth surface, the off-angled GaN substrate could be used …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the slightly distorted unit cell of β-Ga 2 O 3 could be epitaxially grown on the GaN/A 2 O 3 substrate, which might require a relaxation technology of the β-Ga 2 O 3 unit cell to improve device performance. To alleviate the shape-related issues of the β-Ga 2 O 3 growth surface, the off-angled GaN substrate could be used …”
Section: Resultsmentioning
confidence: 99%
“…To alleviate the shape-related issues of the β-Ga 2 O 3 growth surface, the off-angled GaN substrate could be used. 21 The Fermi level and valence band edge of the grown β-Ga 2 O 3 on the GaN/Al 2 O 3 substrate were extracted from the linear extrapolation using UPS, as shown in Figure 5a. The extracted Fermi level and valence band edge were 3.8 and 8.3 eV, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gallium oxide has several polymorphs [9][10][11][12] namely α, β, γ, δ, and κ(ε). Metastable κ(ε)-Ga 2 O 3 polymorph is of particular interest for the development of electronic devices due to its fundamental properties [13] such as the thermal stability up to 700 • C; the high bandgap E g of 4.5-5.0 eV; availability of the ferroelectric properties; the high symmetry of a crystal lattice.…”
Section: Introductionmentioning
confidence: 99%
“…High-quality β-Ga 2 O 3 thin films are heteroepitaxially grown on different substrates Si, GaAs, MgO, and α-Al 2 O 3 via various successful growth methods such as molecular beam epitaxy, low-pressure chemical vapor deposition, metal-organic vapor phase epitaxy, halide vapor phase epitaxy, , pulsed-laser deposition, hot wall metal-organic CVD, and RF magnetron sputtering . The low-cost sapphire substrate has a very large band gap (8.1 eV).…”
Section: Introductionmentioning
confidence: 99%